Potent kinase inhibitors from the Merck KGaA OGHL: Novel hits against Trypanosoma brucei with potential for repurposing - Dize, Darline; Moumbock, Aurélien F. A.; Tchuenguia, Vianey C.; Bougnogolo, Germaine Y.; Nana, Fride S. B.; Monkam, Sandra D. W.; Boyom, Fabrice F. (PLOS Neglected Tropical Diseases, 2025)
African trypanosomiasis remains a critical public health concern, with over 55 million people still at risk of infection. There are several issues associated with the current therapies including toxicity and resistance, which represent the main bottleneck of trypanosomiasis control. Thus, it is urgent to develop novel therapeutic tools with distinct mechanisms of action. The in vitro phenotypic screening of the Merck KGaA Darmstadt German Open Global Health Library (OGHL) against Trypanosoma brucei brucei yielded three potent kinase inhibitors belonging to different chemical series: a phenylcarbonylacrylamide (OGHL00006); a 2,4-di(phenylamino)pyrimidine (OGHL00133); and a 3-(triazol-4-yl)-7-azaindole (OGHL00169). They exhibited low micromolar to nanomolar median inhibitory concentrations (IC50 values of 0.6 µM, 0.007 µM, and 0.25 µM, respectively) and good selectivity when tested on Vero cells (SI > 2). OGHL00006 and OGHL00169 induced a rapid and irreversible growth arrest of T. b. brucei within 4–24 hours of incubation. Interestingly, these two hits have also been reported to display antiplasmodial and/or anthelminthic activities, hinting at a similar mechanism of action across multiple species. Given the significant sequence similarities between the human and trypanosome kinomes, we rationalized the putative mechanisms of action for the identified hits through comparative modeling of protein–ligand complexes. This study suggests promising avenues for drug and/or target repurposing against trypanosomiasis.